2016
DOI: 10.1097/txd.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Enhances NK Cell Activity In Vitro

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…Intriguingly, CD56 dim NK cells from CMV-positive donors had a significantly higher capacity to secrete IFN-γ than those from CMV-negative individuals (Figure 1F). These data are in line with previous reports that established a role for CMV in shaping immune reactivity of CD56 dim NK cells both in vitro and in vivo [34,35], a phenomenon that was not recapitulated in the CD56 neg NK cell subset (Figure 1F). In all, our data suggested that CD56 neg NK cells had reduced cytotoxic capacity and IFN-γ production compared to CD56 dim NK cells, a feature that was further pronounced in the context of CMV / EBV co-infection.…”
Section: Resultssupporting
confidence: 93%
“…Intriguingly, CD56 dim NK cells from CMV-positive donors had a significantly higher capacity to secrete IFN-γ than those from CMV-negative individuals (Figure 1F). These data are in line with previous reports that established a role for CMV in shaping immune reactivity of CD56 dim NK cells both in vitro and in vivo [34,35], a phenomenon that was not recapitulated in the CD56 neg NK cell subset (Figure 1F). In all, our data suggested that CD56 neg NK cells had reduced cytotoxic capacity and IFN-γ production compared to CD56 dim NK cells, a feature that was further pronounced in the context of CMV / EBV co-infection.…”
Section: Resultssupporting
confidence: 93%
“…CD56 dim NK cells expanded after viremia, while long-term after transplant the ratio of CD56 dim to CD56 bright NK cells was equivalent between CMV PCR + and PCR – patients. Delayed repopulation of these memory-like CD56 dim NK cells has previously been associated with CMV disease in stem cell and kidney transplant recipients ( 13 , 14 , 42 ). There is also evidence of long-term persistence of these cells following viremia ( 43 ).…”
Section: Discussionmentioning
confidence: 97%
“…CMV primary infection or reactivation is a significant problem in transplant recipients receiving immunosuppressive therapy, with direct effects from CMV disease and indirect immunopathological effects (12). In SOT, CMV viremia and symptomatic disease are associated with chronic graft dysfunction and rejection (12), and NK and CD8 T cell number and magnitude have been implicated in control of CMV post-transplant and graft outcome (13)(14)(15)(16). For this reason, transplant recipients receive antiviral prophylaxis with additional routine screening for CMV DNA in the periphery to monitor control of infection (17).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, if no such changes in NK phenotype were seen, it would add further support for the conclusion that the recipient had resisted transmission of HCMV from the donor. A single recent publication reports that significant changes in NK phenotype can be seen from 6 months posttransplant in patients with primary CMV infection …”
Section: Suggested Criteria To Evaluate Whether Active or Passive Immmentioning
confidence: 99%